Role of Community Gardens in Development of Housing Estates in Polish Cities - Beata Janowska; Jagoda Łój; Roman Andrzejak (Agronomy, 2022)
The amount of green is relatively low in most cities. Often, the cause of this situation is urban policy which favours developers. Far-reaching urbanization results in various environmental and social problems. In those circumstances, a need for the wider revitalization and reorganization of urban space becomes even more important and necessary. Our article is a review. It discusses the significance of community gardens in Poland due to people’s limited access to private gardens and the growing development of housing estates in cities. In recent decades, cities have developed rapidly in Poland. However, this development was often uncontrolled because very compact building patterns were applied in new housing estates. As a result, in many places the urban tissue lacked common public space. Urban planners adopted a new approach to public goods, including green spaces, and reconsidered the development of cities. Common space was found to be fundamental for the development of the identity of individual neighbourhood groups and, consequently, for social changes. Community gardens are an example of changes introduced to the urban landscape as a consequence of considering common space significant. As a result, local residents can integrate and change their attitude to public space, which is perceived as part of the community. Users gain a sense of community, solidarity, and shared responsibility. The community garden becomes a reason for neighbourhood residents to integrate despite the fact that they may differ in their political views, background, and age. Community gardens are established in a similar way all over the world. However, there might be local differences in the legal system, people’s mentality, and access to land. Community gardens are a new phenomenon in Poland. They are established mainly in big cities, e.g., in Warsaw, Kraków, and Poznań. Community gardens have numerous advantages. Their users are physically active, and they are thus at lower risk of chronic and non-infectious diseases. They grow vegetables and thus change their eating habits. In addition, community gardens reduce stress. Due to gardening, users feel better, broaden their social contacts, participate in cultural events, and enrich their diet. This article shows how the intensive development of housing estates in Poland affects the availability of green areas. The advantages of community gardens in Poland and other countries, methods of plant cultivation and how community gardens functioned during the COVID-19 pandemic are discussed. With this short review, we want to broaden the knowledge about community gardens as their development in Poland is different than in other countries and to encourage their establishment due to the decreasing amount of green space and dense urban development.